The Enhancing Sustainability Reasoning through AI-Supported Scaffolded Academic Reading in EFL Contexts - Ettyani; Ichwan Bagus Airlangga (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study investigates the effect of AI-supported scaffolded academic reading on students’ sustainability reasoning in an EFL context. Using a quasi-experimental design over eight weeks, the research involved twelfth-grade EFL students at a senior high school in Indonesia. The experimental group received AI-assisted scaffolded reading instruction, while the control group participated in conventional reading activities. Data were collected through the Sustainability Reasoning Test (SRT), reflective writing tasks, questionnaires, and classroom observations, then analyzed using t-tests and thematic analysis. The findings show that the experimental group experienced significant improvement in sustainability reasoning, whereas the control group showed minimal progress. Students receiving AI-supported scaffolding demonstrated stronger abilities to identify main claims, evaluate evidence, and construct logical arguments. They also reported greater engagement and confidence in analyzing sustainability-related texts. The study highlights the potential of integrating artificial intelligence with pedagogical scaffolding to enhance academic literacy, deeper comprehension, and sustainability-oriented learning among EFL learners.